The Evaluation of Fission Barrier Height by Fission Toy Model Approach - R. Kurniadi; Z. Suud; Y. S. Perkasa (PPIKSN-BATAN, 2022)
Fission yields are compulsory data on the development of nuclear technology. Therefore, it is necessary to provide complete data. However, the expected experimental data encompass only a tiny fraction of various nuclides; not even all nuclides have fission product data. JENDL and ENDF are databases that have completed the experimental data. These databases were obtained through the process of evaluating experimental data. The evaluation technique used includes the results of theoretical research that has been carried out. Fission Toy Model (FTM) is a fission model proposed to complement the preexisting ones. Each model has advantages and disadvantages. The advantage of the FTM model is that it uses stochastic principle in its calculations.This research aims to obtain a fission barrier through the FTM. The work is related to calculating the fission barrier using the random nature of nucleon position. The calculation technique is basically to take advantage of the random nature of the nucleon position to calculate the Coulomb energy. Then, by calculating several essential points, a data set was obtained that can be used to produce a curve that relates the Coulomb energy to the mass number and the atomic number of a nuclide.The success of this research is indicated by the calculation results that are close to the experimental value compared to other methods.